2010
DOI: 10.3846/jbem.2010.29
|View full text |Cite
|
Sign up to set email alerts
|

Private Capital Flows to Low‐income Countries: The Role of Domestic Financial Sector

Abstract: Abstract.The relationship between private capital flows and growth has been examined extensively in the literature, yet numerous controversies still remain. The study examines the relationships among private capital flows (foreign direct investment, portfolio investment and foreign debt), financial development and economic performance in a sample of 16 low-income developing countries over the period 1988-2006, by employing generalized method of moments (GMM) panel data analysis. We find that private capital fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Theoretically, a country will benefi t from the positive effect of external debt if it has been effi ciently allocated to domestic investment, resulting in a higher rate of growth. In addition, a well-functioning fi nancial institution that supports the investment environment climate will result in a positive impact of private capital fl ow (which includes foreign direct investment, portfolio investment and foreign debt) on economic growth (Choong et al 2010). Furthermore, a country could improve its capability to service debt without crowding out investment.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, a country will benefi t from the positive effect of external debt if it has been effi ciently allocated to domestic investment, resulting in a higher rate of growth. In addition, a well-functioning fi nancial institution that supports the investment environment climate will result in a positive impact of private capital fl ow (which includes foreign direct investment, portfolio investment and foreign debt) on economic growth (Choong et al 2010). Furthermore, a country could improve its capability to service debt without crowding out investment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The issues related to capital fl ight through foreign direct investment and the importance of external debt has started to gain the concern of policy-makers, investors and academics. Several studies that have analyzed the impact of foreign direct investment in stimulating growth are ambiguous, with mixed results (Choong et al 2010) while the impact of external debt on economic growth remains an important and compelling debate with no clear consensus emerging. In retrospect, the high stock of external indebtedness held by some of the developing countries that are associated with a high incidence of default and poverty has underlined the importance of research to investigate this debatable issue.…”
Section: Introductionmentioning
confidence: 99%
“…Since the pivotal works of Romer (1990) and Grossman and Helpman (1991), the long‐run impact of trade on economic growth has largely been deemed positive. Also, the literature notes the relevance of financial development to the growth of an economy, amid capital flows (Agbloyor et al, 2014; Choong, Lam and Yusop, 2010). We sourced all control variables from the World Development Indicators of the World Bank.…”
Section: Methodsmentioning
confidence: 99%
“…On the one hand, large number of studies have documented that surges in foreign capital inflows help promote investments, stimulate economic development, improve resource allocation, interact human capital, deepen domestic financial sector, and encourage positive growth externalities. Examples of these studies include, among others, De Mello (1996Mello ( , 1997, Reisen and Soto (2001), Hermes and Lensink (2003), Alfaro, et al (2004), Buch, et al (2005), Adams (2009), Wang and Wong (2009), Choong, et al (2010), and Azman-Saini, et al (2010). Researchers have also shown that access to international funds help countries in attaining sustainable economic growth, provide benefits associated with international financial integration, and ensure domestic macroeconomic stability [Kose, et al (2009) and Obstfeld (2009)].…”
Section: Introductionmentioning
confidence: 99%